2014
DOI: 10.1371/journal.pone.0092572
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy-Induced Anti-Tumor Immunity Contributes to the Therapeutic Efficacy of Irradiation and Can Be Augmented by CTLA-4 Blockade in a Mouse Model

Abstract: PurposeThere is growing evidence that tumor-specific immune responses play an important role in anti-cancer therapy, including radiotherapy. Using mouse tumor models we demonstrate that irradiation-induced anti-tumor immunity is essential for the therapeutic efficacy of irradiation and can be augmented by modulation of cytotoxic T lymphocyte (CTL) activity.Methods and MaterialsC57BL/6 mice, syngeneic EL4 lymphoma cells, and Lewis lung carcinoma (LL/C) cells were used. Cells were injected into the right femurs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(75 citation statements)
references
References 17 publications
6
68
0
1
Order By: Relevance
“…Moreover, combinations of radiotherapy with immunomodulatory antibodies such as CTLA-4 or PD-1 blocking antibodies have already shown clear synergistic potential (Yoshimoto et al, 2014). As reviewed by Shababi et al, radiotherapy can make tumors more immunogenic by enhancing antigen presentation, antigen uptake and the secretion of immunostimulatory factors (Shahabi et al, 2015).…”
Section: Radiotherapymentioning
confidence: 99%
“…Moreover, combinations of radiotherapy with immunomodulatory antibodies such as CTLA-4 or PD-1 blocking antibodies have already shown clear synergistic potential (Yoshimoto et al, 2014). As reviewed by Shababi et al, radiotherapy can make tumors more immunogenic by enhancing antigen presentation, antigen uptake and the secretion of immunostimulatory factors (Shahabi et al, 2015).…”
Section: Radiotherapymentioning
confidence: 99%
“…Indeed, some evidence suggests that immunogenic cell death contributes to the efficacy of hypofractionated or single-dose radiotherapy (37, 69, 70). However, data regarding the influence of dose and fractionation are conflicting, thus warranting a critical review of the dose dependence of immune activation.…”
Section: Radiation-induced Enhancement Of Immune Activitymentioning
confidence: 99%
“…In another series of experiments involving mice implanted with Lewis lung carcinoma cells, Yoshimoto and colleagues found that radiation (30 Gy) combined with CTLA4 blockade extended both tumor growth delay and median survival time (56 days) compared with radiation alone (46 days) or anti-CTLA4 IgG alone (<40 days). They also noted that administering anti-CD8 antibody with radiation further extended median survival time and tumor growth inhibition [25]. In other studies using tumor-infiltrating lymphocytes after anti-CTLA4 plus radiation in a melanoma mouse model, Victor and colleagues noted that anti-CTLA4 antibody decreased the number of Tregs, whereas radiation increased T-cell receptor (TCR) diversity.…”
Section: Immune Checkpointsmentioning
confidence: 99%